Analisis Faktor-faktor yang Mempengaruhi Mahasiswa Dalam Keputusan Pembelian Handphone Android: (Studi Kasus Pada Mahasiswa Pendidikan Ekonomi FKIP Universitas Palangka Raya) - Datri Widati; Kuwing Baboe; Sundari Sundari; Rinto Alexandro (FKIP, Universitas Palangka Raya, 2023)
Android phones or better known as smartphones are one of the products that are in great demand by the public today, especially among students. Because for students android smsrtphone is a necessity. The wide variety of product choices, brand choices, design choices, and price options offered by each company will of course trigger differences in consumer reasons for choosing which android phone best suits their individual tastes. The purpose of this study is to analyze whether cultural factors, social factors, personal factors and psychological factors influence the decisions of economic education students FKIP Palangka Raya University in buying an android phone. To determine the research subject, the researcher selected Economic Education Students at the FKIP Univercity of Palangka Raya, class of 2017 and class of 2018 who bought and used Vivo, Oppo, and Xioami android phones. This research uses qualitative methods, for the data collection procedure is carried out by distributing questions according to interview guidelines via google forms, then further interviews are carried out through zoom meetings with informants and then documented for data analysis that has been obtained. The data thet has been collected will be checked for the validity of the data by means of a credibility test, transferability test, dependability test, and cinfirmability test. The results of this study indicate thet cultural factors, social factors, personal factors and psychological factors as a whole affet the Decisions of Economic Edication Student FKIP Palangka Raya University in making decisions to buy Vivo, Oppo, and Xioami android mabile phones. However each variable has a different level of significance. If sorted from dominating, personal factors are in the highest position, then social factors, cultural factors and finally psychological factors